Maternal exposure to intimate partner abuse before birth is associated with autism spectrum disorder in offspring. (January 2016) - Roberts, Andrea L; Lyall, Kristen; Rich-Edwards, Janet W; Ascherio, Alberto; Weisskopf, Marc G
We sought to determine whether maternal (a) physical harm from intimate partner abuse during pregnancy or (b) sexual, emotional, or physical abuse before birth increased risk of autism spectrum disorder. We calculated risk ratios for autism spectrum disorder associated with abuse in a population-based cohort of women and their children (54, 512 controls, 451 cases). Physical harm from abuse during pregnancy was not associated with autism spectrum disorder. However, autism spectrum disorder risk was increased in children of women who reported fear of partner or sexual, emotional, or physical abuse in the 2 years before the birth year (abuse in the year before the birth year: risk ratio = 1.58, 95% confidence interval = 1.04, 2.40; abuse in both of the 2 years before the birth year: risk ratio = 2.16, 95% confidence interval = 1.33, 3.50). Within-family results were similar, although did not reach statistical significance. Association of intimate partner abuse before the child's birth year with autism spectrum disorder in the child was not accounted for by gestation length, birth weight, maternal smoking or alcohol consumption during pregnancy, gestational diabetes, preeclampsia, or history of induced abortion.